DISCOURSE ANALYSIS OF POND'S MEN'S ADVERTISING “LELAKIMASAKINI” VERSION OF RIO DEWANTO - Fauzi, Abas (Capture : Jurnal Seni Media Rekam, 2018)
This research discusses how advertising producers provide a new formula for men nowdays. Through such as advertising, manufacturers are trying to create a standard male nowdays with efforts of disciplining the body. Pond's Mens it self always bring up the ad with a new concept when they put out a new product variant. The man of today is a manifestation of cooperation between the pond's makes Rio Dewanto as a brand ambassador. This research uses critical discourse analysis, model which Norman Fairclough classifies three dimensions of discourse consisting of text, discourse practices and socio cultural practices. The dimensions of the text simultaneously has three functions, namely the representation, relationships, and identity. The results showed that the ads were shown to men as a disciplinary body's efforts. In addition, this commercial bias occurs in practice meaning between scenes in the ad with the discourse of the present men.